Aktualisasi Ajaran Ki Ageng Suryomentaram Sebagai Basis Pendidikan Karakter - Kamal, Faisal; Wahyuningrum, Zulfa Indra (PANCAR, 2017)
The realization of human character is the core in an educational process. As educators are obliged to inculcate the values of character against his prot?g? through the learning process. Through the introduction of history, educators can introduce local figures, who in the past have thought beyond his time. The figure is of Ki Ageng Suryomentaram, assessment against his teachings as a reference is the implementation of learning for the young generation today. This study attempts to show that of Ki Ageng Suryomentaram figure understated, and a fighter worthy of being role models. About how to become a whole person which can be found at the core of his teachings. This research is a study of character, i.e. Ki Ageng Suryomentaram. This research uses descriptive qualitative approach with review of the literature (library research) in its collection. For the collection of data using methods of documentation, while its analysis use analysis of the content (content analysis).